A calcium peroxide incorporated oxygen releasing chitosan-PVA patch for Diabetic wound healing - Asad Ullah (4524541) (2023)
Impaired wound healing is a major healthcare problem in patients with diabetes often resulting in gangrene, microbial infection and amputation of affected limb. The delay or absence in healing process arises from several abnormalities, among them chronic hypoxia is a major concern due to its associated issues such as lack of collagen deposition, epithelization, fibroplasia, angiogenesis, and resistance to infections at the wound site. To address hypoxia, delivery of oxygen at the wound site through oxygen releasing agents have been proven to be effective therapeutics. Several oxygen releasing nanoparticles such as Sodium Percarbonate (SPC), Calcium Peroxide (CPO), Hydrogen Peroxide, Magnesium Peroxide (MPO) have been investigated in wound healing application. However, the uncontrolled/burst release of these nanotherapeutic agents and its accompanied cytotoxicity pose a barrier in expediting the healing process. In this study, a Chitosan-Polyvinyl alcohol (CS-PVA) based hydrogel containing oxygen releasing nanoparticle, calcium peroxide (CPO) was constructed to provide a slow and sustained delivery of oxygen for at least 5 days. In-vitro cell culture studies with this material using fibroblast and endothelial cell line exhibited improved biocompatibility, cell viability and enhanced proliferation in comparison with the control group. Additionally, cell migration study using scratch assay method showed superior cell migration ability of our proposed materials. Furthermore, In vivo study using diabetic rat model showed accelerated wound closure rate compared to untreated control wounds. Other Information Published in: Biomedicine & Pharmacotherapy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.biopha.2023.115156 Additional institutions affiliated with: Pak-Qatar Family Takaful Limited (PQFTL), Dow University of Health Sciences Qatar and Dow International Medical College – DUHSQ